ChemInform Abstract: Gold(I)‐Catalyzed Cyclization/Nucleophilic Substitution of 1‐(N‐Sulfonylazetidin‐2‐yl) Ynones into N‐Sulfonylpyrrolin‐4‐ones. Issue 26 (June 2016) - Miaskiewicz, Solene; Weibel, Jean‐Marc; Pale, Patrick; Blanc, Aurelien
Abstract: A series of N‐tosylpyrrolin‐4‐ones is readily obtained by gold‐catalyzed reaction of 1‐(N‐tosylazetidin‐2‐yl)ynones (I) with alcohols.